New drugs in breast cancer treatment - Rolski, Janusz; Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
Cytotoxic chemotherapy, endocrine treatment and targeted therapies are important for the treatment of women with advanced breast cancer. A variety of agents are effective, alone or in combination. The clinical activity and side effects of many agents, as well as principles of using systemic treatment are reviewed. Recent advances in the systemic treatment of breast cancer include important studies on the role of new cytotoxic agents, modification of available agents to reduce side effects and the availability of oral chemotherapeutics. The combination of chemotherapy with novel biological agents may improve outcomes for women with breast cancer. The growing availability of such biological therapies given in combination with chemotherapy may mean better survival in the future for women with advanced breast cancer. The most promising new group of cytotoxic chemotherapeutic agents are drugs that poison the mitotic spindle, such as taxanes and vinca alkaloids (vinorelbine). Oral administration of 5-Fu therapy affords the favourable pharmacokinetic feature of continuous intravenous infusion, without the requirement of paraenteral infusion. Novel liposomal delivery systems allow maximum bioavailability with minimal toxicity. Evaluation of intracellular signaling pathways initiated by HER2 activation is of major interest in the development of novel therapeutics. Other important areas under clinical development are farnelysation of various proteins, antiangiogenesis agents and identification of specific genetic anomalies as targets for intervention.